1978
DOI: 10.2337/diab.27.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Vitreous Fluorophotometry: A Sensitive Technique for Measuring Early Breakdown of the Blood-retinal Barrier in Young Diabetic Patients

Abstract: Vitreous and aqueous humor fluorescein concentrations were measured one hour after graded intravenous fluorescein was given to 20 juvenile diabetics, ages 20 to 40, with and without retinopathy, and to 12 controls of similar age. Vitreous fluorescein concentrations were significantly higher in diabetics, indicating breakdown of the blood-retinal barrier. Mean vitreous fluorescein values were 10.66 +/- 0.65 for the diabetics and 4.28 +/- 0.37 ng./ml. for the controls. Breakdown of the blood-retinal barrier was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(31 citation statements)
references
References 0 publications
3
26
2
Order By: Relevance
“…At the time of this study, six of our patients had demonstrable clinical retinopathy confirmed by fluorescein angiography. Although the remaining six had not undergone fluorescein studies, it is likely that they too had abnormalities of the blood-retinal barrier because the prevalence of capillary leakage (as detected by the sensitive and specific [44] technique of vitreous fluorophotometry) is practically 100%, even very shortly after the diagnosis of diabetes and while fluorescein angiograms are still perfectly normal (4,44,45). The effectiveness of dopamine as a growth hormone secretagogue in our diabetic patients shares the characteristics of the abnormal vitreous fluorophotometry in the general diabetic population: it is a consistent finding and its occurrence is independent of the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of this study, six of our patients had demonstrable clinical retinopathy confirmed by fluorescein angiography. Although the remaining six had not undergone fluorescein studies, it is likely that they too had abnormalities of the blood-retinal barrier because the prevalence of capillary leakage (as detected by the sensitive and specific [44] technique of vitreous fluorophotometry) is practically 100%, even very shortly after the diagnosis of diabetes and while fluorescein angiograms are still perfectly normal (4,44,45). The effectiveness of dopamine as a growth hormone secretagogue in our diabetic patients shares the characteristics of the abnormal vitreous fluorophotometry in the general diabetic population: it is a consistent finding and its occurrence is independent of the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal transcapillary escape rate of albumin [95], abnormal urinary albumin excretion during exercise [96] and leakage of fluorescein from the retinal vessels into the vitreous and the anterior segment of the eye have been described [97][98][99][100][101]. Several reports indicate that strict control of blood sugar levels reduces or abolishes these manifestations of functional microangiopathy [95][96][97].…”
Section: Functional Microangiopathy Organ Size and Blood Compositionmentioning
confidence: 99%
“…VF brought an important clinical contribution for quantifying BRB permeability in DR and is of particular interest in the preclinical stage since diabetic eyes show increased permeability values even in apparently normal ocular fundi (27,28).…”
Section: Vfmentioning
confidence: 99%